A process evaluation of the Communication for Healthy Communities adolescent health program in Uganda. Issue 1 (25th November 2019) - Nalukwago, Judith; Alaii, Jane; van den Borne, Bart; Bukuluki, Paul Mukisa; Kimbowa, Musa; Bockh, Emily; Coutinho, Sheila Marunga; Crutzen, Rik
Abstract: This study is a process evaluation of an adolescent-focused intervention of the USAID Communication for Healthy Communities program, in Uganda. We used mixed methods including observation, consultations and review of program documents to collect data on program coverage, reach and factors influencing implementation. Findings show that program activities were successfully implemented through collaborative partnerships with service partners and the community. Interpersonal communication complemented by mass-media messaging was effective in reaching and empowering adolescents with health information to make informed choices for behavior change. The program used theoretical frameworks to guide targeted interventions through audience segmentation and community empowerment. Targeted mass-media messaging and placement was found to be pertinent for program reach. Working through existing community structures is important for an effective reach of health promotion programs. Lessons identified for scaling-up adolescent health programs include the need to harmonize training and deployment of community champions by development partners, recruit audience-specific influential champions and link income-generating activities to health education interventions. There is thus need to collaboratively develop and institutionalize effective monitoring and evaluation strategies during program inception and design phases for appropriate accountability, ownership and a continuation of gains.